2007
DOI: 10.1007/s00441-006-0357-3
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic approach to the investigation of early events involved in vascular smooth muscle cell activation

Abstract: Vascular smooth muscle cells (VSMC) are mature cells that maintain great plasticity. This distinctive feature is the basis of the VSMC migration and proliferation involved in cardiovascular diseases. We have used a proteomic approach to the molecular changes that promote the switch of VSMC from having a quiescent to activatedproliferating phenotype. In particular, we have focused on modulations occurring during tyrosine-phosphorylation following cell activation by serum or single growth factors, such as insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
(29 reference statements)
0
11
1
Order By: Relevance
“…Hence, contrary to our expectations, our data indicated that the proteomic differences that we detected were a response to medium shift per se rather than a proteome profile for the cells grown in a specific medium. The presence of growth factors has been shown to result in protein expression changes in SMCs in several previous studies (38)(39)(40). However, in our study, although we observed changes, the changes were not in response to the presence of growth factors.…”
Section: Discussioncontrasting
confidence: 90%
“…Hence, contrary to our expectations, our data indicated that the proteomic differences that we detected were a response to medium shift per se rather than a proteome profile for the cells grown in a specific medium. The presence of growth factors has been shown to result in protein expression changes in SMCs in several previous studies (38)(39)(40). However, in our study, although we observed changes, the changes were not in response to the presence of growth factors.…”
Section: Discussioncontrasting
confidence: 90%
“…Johansson et al 1997;Kacem et al 1996). Even if this is a considerable simplification (Boccardi et al 2007), changes in expression of these cytoskeletal proteins should reflect at least the basic changes of the mechanical properties of the vessel wall due to surgery sufficiently.…”
Section: Elastin Length Density In the Aortic Wall Decreased In Timementioning
confidence: 98%
“…VSMC are able to modulate their phenotype in response to injury and mechanical stimuli (Miyazaki et al 2002;Owens et al 2004;Yoshigi et al 2000), changing the mechanical properties of the vessel wall. In general, VSMC phenotype switches from contractile to synthetic after injury (Boccardi et al 2007;Miyazaki et al 2002;Owens et al 2004;Shanahan and Weissberg 1999).…”
Section: Elastin Length Density In the Aortic Wall Decreased In Timementioning
confidence: 99%
“…VSMCs can modulate their phenotype from contractile (more actin and desmin) to synthesis (less actin and desmin, more vimentin, and higher proliferative activity) (Miyazaki et al, 2002;Owens et al, 2004;Boccardi et al, 2007). Actin, desmin, and vimentin can be detected in both porcine and human aortic samples using the same antibodies, their immunopositivity is robust and therefore easily to be quantified Houdek et al, 2013;Eberlova et al, 2013).…”
Section: Introductionmentioning
confidence: 97%